2006
DOI: 10.1161/01.res.0000209968.66606.10
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 Blocks Vascular Endothelial Growth Factor-Induced Endothelial Cell Motility and Tube Formation via Inhibition of Calpain

Abstract: Abstract-Angiogenesis plays a critical role in wound repair. Endothelial cells present CXC receptor 3 (CXCR3) for chemokines expressed late in wound regeneration. To understand the physiological role CXCR3 plays in regulating endothelial function, we analyzed the ability of a CXCR3 ligand, IP-10 (CXCL10), to influence endothelial cell tube formation. Treatment of endothelial cells with IP-10 in the presence of vascular endothelial growth factor (VEGF) inhibited tube formation on growth factor-reduced Matrigel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(249 citation statements)
references
References 26 publications
(35 reference statements)
8
241
0
Order By: Relevance
“…This conditional, post-natal expression was required as constitutive ablation of PLCg is embryonic lethal (Ji et al, 1998b). Furthermore, by limiting expression to the target epithelial cells, we avoid issues of altering the microenvironment of the primary and metastatic tumor sites, as well as affecting tumor-associated angiogenesis (Bodnar et al, 2006). We chose a reversible, inducible system rather than conditional gene deletion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This conditional, post-natal expression was required as constitutive ablation of PLCg is embryonic lethal (Ji et al, 1998b). Furthermore, by limiting expression to the target epithelial cells, we avoid issues of altering the microenvironment of the primary and metastatic tumor sites, as well as affecting tumor-associated angiogenesis (Bodnar et al, 2006). We chose a reversible, inducible system rather than conditional gene deletion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…40,[88][89][90][91] These ligandreceptor interactions reduce fibroblast and endothelial motility while increasing keratinocyte migration. 67,92,93 It is proposed that this signaling axis allows wounds to transition through remodeling resulting in the characteristic appearance of scar tissue with densely packed collagen bundles and reduced elastin. 94,95 Wound contraction secondary to myofibroblast action begins in the proliferative phase, but continues during remodeling.…”
Section: Remodeling Phasementioning
confidence: 99%
“…1 and Table 1). It is likely that VEGF 35,36) and fluid shear stress 13,37,38) are representative activators of calpain systems in ECs under physiological conditions. ECs exhibit measurable calpain activity even under unstimulated conditions 39,40) , which may be due to spontaneous Ca 2+ mobilization in the cells 41) .…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%
“…Mechanistically, calpainmediated regulation of small GTPases 13,40) as well as calpain-induced proteolysis of focal adhesion proteins 37) during EC dynamics has been documented previously. Accordingly, calpain systems appear to play key roles in angiogenesis 36,38) , wound closure 39) and maintenance of barrier functions 13,40) in ECs. In addition to motility responses, it has been reported that nitric oxide (NO) production in ECs is modulated through calpain-induced proteolysis of HSP90 42) or calpain-regulated PI3K/AMPK signaling 35) .…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%